2022
DOI: 10.7759/cureus.22662
|View full text |Cite
|
Sign up to set email alerts
|

The Tyranny of Distance: How Hospital Transfer Affects Time to Surgery for Hip Fracture Patients

Abstract: IntroductionIn Western Australia, vast distances between hospitals can limit a patient's access to timely surgical intervention. The aim was to examine the effect of patient location on outcomes. MethodsHip fracture data from all operative cases at the major Western Australian hospitals between 2015 and 2019 was retrospectively reviewed. A total of 5691 patients were separated into three groups based on hospital of first presentation -directly to the operative hospital (metropolitan), a hospital less than 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Our findings agree with the previous evidence exploring the relationship between transfer status and delays to surgery [11,[13][14][15][16], except for one Irish study which found no differences in the odds of achieving timely surgery between the two groups [12]. This could be because Ireland's geography and healthcare system varies from Scotland's, and they utilised a target time of 48 h. The study was also conducted ten years ago, when demands on orthopaedic services were less and patients were not as complicated [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings agree with the previous evidence exploring the relationship between transfer status and delays to surgery [11,[13][14][15][16], except for one Irish study which found no differences in the odds of achieving timely surgery between the two groups [12]. This could be because Ireland's geography and healthcare system varies from Scotland's, and they utilised a target time of 48 h. The study was also conducted ten years ago, when demands on orthopaedic services were less and patients were not as complicated [25].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, delayed surgery has previously been associated with adverse postoperative outcomes in large meta-analysis, including mortality rates, complications, and extended hospital stays [9,10]. While limited international studies have explored the associated between hospital transfer and delay in surgical management [11][12][13][14][15][16], none however have addressed the unique geographical challenges faced by Scotland and the associated large rural population, particularly in the Highlands and Islands. This means that several patients do not have direct access to hospitals with hip fracture services, and instead initially present to small local units designed to manage rehabilitation or minor injuries.…”
Section: Introductionmentioning
confidence: 99%
“… 20 In this study, we found that delayed admission is a main cause for long interval from injury to operation. In fact, the effect of delayed admission on surgical delay is nonnegligible, especially in tertiary referral trauma centers, because a large number of patients are transferred from relatively remote hospitals, which has been confirmed by Marley et al 21 In addition, we observed a 10% increased risk of early infections for each day of surgical delay, which could be explained by the consumption and imbalance of complement cascade components, and the systemic inflammatory response syndrome (SIRS) secondary to acute trauma. 22 , 23 However, the arbitrary decision on interventions applied to decrease preoperative stay does not necessarily translate into better therapeutic effect, as for geriatric trauma patients, delayed surgery is largely due to the requirement of more time to optimize the poor medical conditions or unstable hemodynamic conditions before surgery, eg, frailty, undesirable soft-tissue conditions, and insulin-dependent.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the optimal timing of hip fracture surgery was controversial, and most of the studies only considered the time from admission to surgery [17]. In many hospitals, especially tertiary referral trauma centers, the impact of delayed admission on the time to surgery cannot be ignored because some of the patients were referred from relatively remote hospitals and often in serious condition [11]. Therefore, we designed a large sample size study for the relationship between the time from injury to surgery and IHPOP and obtained more reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…In a most recent study, Shen et al [6] analyzed the clinical data of 1,118 Asian elderly patients with hip fracture and found a nonlinear S-shaped relationship between POP risk and the time from admission to surgery, but they did not take the time from injury to admission into consideration. In fact, the effect of delay to admission on time to surgery is not negligible, especially in tertiary referral trauma centers because a large number of patients are transferred from relatively remote hospitals, which was emphasized in the study by Marley et al [11]. In the other studies attempting to identify the risk factors related to POP after hip fracture, the sample size was relatively small [7, 8], or delay to operation was not noted or not well illuminated [1, 4].…”
Section: Introductionmentioning
confidence: 99%